CAUSEWAY BUILDING DAMAGE ANALYSIS (Case Study of Torobulu Ferry Port Crossing) - Aswad, Nini H; M, Saltiawan (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2023)
Torobulu Port has been protected from waves by a 238-meter causeway. This study evaluates the performance of the Causeway building and the function of the Torobulu Port building. The CERC technique (1984) was utilized to calculate wave period height, whereas the circular letter of the minister of public works No. 01/SE/M/2011 on operational rules and maintenance of coastal safety buildings was utilized to calculate building condition index. This analysis determined that the causeway is still non-overtopping, so it continues to safeguard the port region from wave threats. The study of the building condition index reveals favorable results, with a value of 1.20 and an index of 0.0 1.15, allowing for physical condition and function-based action recommendations.